2018
DOI: 10.1177/1557988317750989
|View full text |Cite
|
Sign up to set email alerts
|

Research Brief: Self-Reports of a Constellation of Persistent Antiandrogenic, Estrogenic, Physical, and Psychological Effects of Finasteride Usage Among Men

Abstract: Our research objective is to understand more, through subjective, self-reports on discussion boards/forums, persons’ experiences associated with the use of drugs that alter androgen metabolism, such as finasteride. Finasteride is an orally active, specific inhibitor of 5α-reductase, which is localized to many androgen-dependent tissues. Finasteride inhibits the conversion of testosterone (T) to dihydrotestosterone (DHT), and is commonly used to treat benign prostatic hypertrophy (BPH) and male pattern baldness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…Together with the reduction in saccharin or sucrose preference, this index has been long regarded as one of the most robust predictors of depression-like responses in animal models [42]. From this perspective, our findings were consistent with clinical reports indicating the association of FIN with depressive symptoms, including behavioral apathy and anhedonia [43]. Our experiments revealed that FIN yielded similar effects on stress reactivity in both sexes as well as in castrated males.…”
Section: Discussionsupporting
confidence: 89%
“…Together with the reduction in saccharin or sucrose preference, this index has been long regarded as one of the most robust predictors of depression-like responses in animal models [42]. From this perspective, our findings were consistent with clinical reports indicating the association of FIN with depressive symptoms, including behavioral apathy and anhedonia [43]. Our experiments revealed that FIN yielded similar effects on stress reactivity in both sexes as well as in castrated males.…”
Section: Discussionsupporting
confidence: 89%
“…Other side effects reported following treatment with finasteride are linked to the psychological sphere, even if there is a lack of published data and evidence is mostly related to self-reports by patients [ 32 ]. Only 2% of patients treated by the surveyed dermatologists reported diminished quality of life, and eventually anhedonia (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 1, people with high ASQ scores and those with low ASQ scores have certain overlap in the daily speech features, which is the reason for the presence of noise in the sampled data on a daily basis. So, sampling weekly is a good way to avoid the instability of microdata; in addition, it can supplement the scarcity of macrodata; there are 64 samples from 16 people for 4 weeks, which is enough to support training a simple machine learning model [17].…”
Section: Multisensor Feature Compression Based On Pcamentioning
confidence: 99%